2018
DOI: 10.1016/j.csr.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of organic carbon in surface sediments of a summer hypoxic region in the coastal waters of northern Shandong Peninsula

Abstract: The geochemistry of sedimentary organic matter (SOM) in coastal areas is complex due to its multiple sources and intricate hydrological features. In this study, the biogenic element concentrations and stable carbon (δ 13 C) and nitrogen (δ 15 N) isotopic compositions in the coastal surface sediments of northern Shandong Peninsula, along with some parameters related to water quality, were analyzed to investigate the temporal-spatial variations in SOM and the processes that control its distribution. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 76 publications
(91 reference statements)
1
27
0
Order By: Relevance
“…The differences in TOC and TN between spring and summer suggested that labile OM decomposed during the investigation period [55]. The seasonal variation pattern of TOC and TN in the surface sediment of ZJB was different from that in the coastal area of northern Shandong Peninsula (a temperate coastal area), where TOC and TN concentrations were significantly higher in summer than in spring [14]. The relatively high temperature in ZJB (a subtropical bay) is more conducive to the decomposition of OM and reduces the accumulation of OM [56].…”
Section: Toc and Tnmentioning
confidence: 90%
See 4 more Smart Citations
“…The differences in TOC and TN between spring and summer suggested that labile OM decomposed during the investigation period [55]. The seasonal variation pattern of TOC and TN in the surface sediment of ZJB was different from that in the coastal area of northern Shandong Peninsula (a temperate coastal area), where TOC and TN concentrations were significantly higher in summer than in spring [14]. The relatively high temperature in ZJB (a subtropical bay) is more conducive to the decomposition of OM and reduces the accumulation of OM [56].…”
Section: Toc and Tnmentioning
confidence: 90%
“…Surface sediment samples were collected using a stainless steel grab sampler. The sediment surface layer (0-2 cm) was collected at each sampling site [14,23,29]. After collection, the samples were homogenized and placed into sterile polyethylene bags, sealed, and kept on ice in a cooler during transport.…”
Section: Sampling and Analysesmentioning
confidence: 99%
See 3 more Smart Citations